Cleavage of SNAP‐25 ameliorates cancer pain in a mouse model of melanoma. (15th June 2016) - Olbrich, K.; Costard, L.; Möser, C.V.; Syhr, K.M.J.; King‐Himmelreich, T.S.; Wolters, M.C.; Schmidtko, A.; Geisslinger, G.; Niederberger, E.
Abstract: Background: Cancer pain is associated with increased pain sensitivity to noxious (hyperalgesia) and normally innocuous (allodynia) stimuli due to activation of nociceptors by tumour‐derived mediators or tumour infiltration of nerves. The pain sensitization is accompanied by modifications in gene expression, but specifically regulated genes are largely unknown. The 25 kDa synaptosomal‐associated protein (SNAP‐25) is involved in chemical neurotransmission at the synaptic cleft. Its inhibition by Botulinum neurotoxin A (BoNT/A) has been associated with antinociceptive effects in migraine, inflammatory and neuropathic pain. However, its potential to reduce tumour‐associated pain remains to be clarified. Methods: We applied a melanoma model of tumour pain in C57BL/6 mice and investigated SNAP‐25 expression and regulation by qRT‐PCR, Western Blot and immunofluorescence as well as tumour‐associated mechanical allodynia with and without BoNT/A treatment. Results: We found increased SNAP‐25 expression in the dorsal root ganglia and the sciatic nerve. Intraplantar injection of BoNT/A induced the cleavage of SNAP‐25 in these tissues and was associated with decreased mechanical allodynia after therapeutic treatment at early and late stages of tumour pain while the tumour size was not affected. Conclusions: Our data indicate that SNAP‐25 plays a role in tumour pain but has no influence on the initiation and progression of skin cancer. Its cleavage inhibits the development of allodynia in the mouse melanoma model and might be useful as new therapeutic approach for the treatment of cancer pain. What does this study add?: SNAP‐25 is differentially regulated during melanoma‐induced tumour pain. Its cleavage by BoNT/A might be a suitable therapeutic option for tumour pain patients since tumour‐associated pain can be strongly and significantly reduced after preventive and therapeutic BoNT/A treatment, respectively.